PengaruhReligiusitas dan Kepemimpinan Transformasional terhadap KinerjaGuru melalui Mediasi Organizational Citizenship Behavior - Maesaroh, Siti; Asbari, Masduki; Hutagalung, Dhaniel; Mustofa, Mustofa; Agistiawati, Eva; Basuki, Sucipto; Radita, Fatrilia Rasyi; Nurasiah, Nurasiah; Yulia, Yayah; Singgih, Eman; Chidir, Gusli (EduPsyCouns: Journal of Education, Psychology and Counseling, 2020)
This study aimed to measure the effect of transformational leadership and religiosity on the teacher performance of private schools teachers in Tangerang which are mediated by organizational citizenship behavior. Data collection was done by simple random sampling via electronic to the private schools teacher population in Tangerang. The returned and valid questionnaire results were 224 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that religiosity have a positive and significant effect on the teacher performance, both directly and indirectly through mediating organizational citizenship behavior. Meanwhile, transformatonal leadership have not significant effect on the teacher performance, both directly and indirectly through mediating organizational citizenship behavior. This new research proposed a model for building the teacher performance among the private school teachers in Tangerang through enhancing transformational leadership and religiosity with organizational citizenship behavior as a mediator. This research could pave the way to improve teacher readiness in facing the era of education 4.0.